IMPLEMENTATION OF MAZE GAMES IN LEARNING FOR CHILDREN'S COGNITIVE DEVELOPMENT AT RA AL-KHAIRAT - Faizah, Noer; Ainol, Ainol; Kiromi, Ivonne Hafidlatil (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to improve the cognitive development of group B children. Because cognitive ability is a part that is useful for the development of a child's brain, it is referred to as an aspect of development that emerges and develops rapidly at an early age and must be stimulated from an early age. early age. The descriptive qualitative method is used in this type of research. research methods that produce descriptive data in the form of observable behavior and the written or spoken words of individuals are known as qualitative research. The play method teaches people psychomotor skills by showing them how to do something and then practicing it in play. Ten children from group B, including three boys and seven girls, were the subjects of the study. Children's cognitive development is a subject of inquiry. The study found that playing maze games can help children's early cognitive skills grow and develop to their full potential, especially during the golden years. Teacher motivation, as well as the availability of adequate facilities and infrastructure, contribute to children's cognitive development through the use of maze games.